2011
DOI: 10.1128/aac.00930-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Mode of Inhibition of Class A SHV-1 β-Lactamases Revealed by Boronic Acid Transition State Inhibitors

Abstract: Boronic acid transition state inhibitors (BATSIs) are potent class A and C ␤-lactamase inactivators and are of particular interest due to their reversible nature mimicking the transition state. Here, we present structural and kinetic data describing the inhibition of the SHV-1 ␤-lactamase, a clinically important enzyme found in Klebsiella pneumoniae, by BATSI compounds possessing the R1 side chains of ceftazidime and cefoperazone and designed variants of the latter, compounds 1 and 2. The ceftazidime and cefop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Studies have shown analogs of ampicillin, cephalothin, and cefoperazone to be inhibitors of clinically relevant class A and C ␤-lactamases in the nM range (i.e., 9.3 nM, 420 nM, and 11 nM for K. pneumoniae SHV and for AmpCs from P. aeruginosa and Acinetobacter spp., respectively) (Fig. 3b) (53)(54)(55)(56). These compounds are still preclinical.…”
Section: Boronic Acid ␤-Lactamase Inhibitorsmentioning
confidence: 98%
“…Studies have shown analogs of ampicillin, cephalothin, and cefoperazone to be inhibitors of clinically relevant class A and C ␤-lactamases in the nM range (i.e., 9.3 nM, 420 nM, and 11 nM for K. pneumoniae SHV and for AmpCs from P. aeruginosa and Acinetobacter spp., respectively) (Fig. 3b) (53)(54)(55)(56). These compounds are still preclinical.…”
Section: Boronic Acid ␤-Lactamase Inhibitorsmentioning
confidence: 98%
“…This model takes into account the crystallographic intermediates captured in two previous studies (15,17).…”
Section: Synthesismentioning
confidence: 99%
“…In a parallel quest, BATSIs were studied and optimized for a variety of ␤-lactamase enzymes (7,(13)(14)(15)(16)(17)(18). Mechanistically, the boronic inhibitors act by binding to the active site of the enzyme, where they sterically resemble the quaternary transition state of the ␤-lactam hydrolysis reaction and occupy the active site with high affinity, leading to inhibition in a reversible competitive manner (9).…”
mentioning
confidence: 99%
“…As stated above, an emerging notion in the discovery of novel BLIs is to utilize boronic acid transition state analogs (BATSIs) to inhibit serine ␤-lactamases such as KPC-2 and SHV-1 (12)(13)(14). Such an approach has led to several potent inhibitor compounds (15,16).…”
mentioning
confidence: 99%